Fecal microbiota transplantation: present and future - Ra Ri Cha; Irene Sonu (Clinical Endoscopy)
Fecal microbiota transplantation (FMT) involves transplanting fecal matter from healthy donors into patients with gut dysbiosis to restore microbial balance. It has been proven to be highly effective in treating recurrent Clostridioides difficile infection (CDI), and United States Food and Drug Administration-approved microbiome-based therapies, such as REBYOTA (fecal microbiota live-jslm) and VOWST (fecal microbiota spores live-brpk), offer promising treatment options. Although FMT is widely used to treat recurrent CDI, its use in gastrointestinal and metabolic diseases remains limited. Future research directions include optimizing donor selection, understanding microbial mechanisms, and exploring the potential of FMT for treating other diseases. Ongoing research not only aims to broaden its indications but also improves its safety and efficacy. Emerging therapies such as VE303 (Vedanta) are being studied to refine treatment approaches and expand the use of microbiota-based therapies. Further studies are needed to standardize guidelines, improve patient outcomes, and better define the role of FMT in the treatment of diseases beyond recurrent CDI.